The role of context in shaping narratives of plurilingual identity: The case of non-language majors studying abroad - Marinov, Sanja; Soule, Maria Victoria; Cots, Josep Maria (My University, 2021)
This chapter examines the role of context, understood here as a site for social practices in particular settings, before and during study abroad (SA) in the development of students’ plurilingual identities. In particular, we focus on different levels of contextual constraints and opportunities to which students who are non-language majors refer in semi-structured interviews. The study is based on an analysis of narratives of Erasmus students spending their SA sojourn in three different Mediterranean countries (Spain, Cyprus, and Croatia). The recurring themes from the interviews generated five dimensions of context that played a role in shaping narratives of the participants’ plurilingual identity.
Keywords: Role of context; Study abroad